1998
DOI: 10.1016/s0022-0248(97)00825-7
|View full text |Cite
|
Sign up to set email alerts
|

Flow-induced changes of the morphological stability in directional solidification: localized morphologies

Abstract: Steady, two-dimensional cellular convection is impressed upon a solid-liquid interface undergoing directional solidification. When the wave length 27r / a of the convection is very long compared to that, 27r / ß, of the morphological instability, the interface is sheared by "parallel" remote flow periodic in the flow direction.When the shear is taken to be constant instead of spatially periodic, a new formulation shows how a whole family of shear flows can be analyzed in a common way and how the physical mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 18 publications
1
8
0
1
Order By: Relevance
“…Such instabilities have been analyzed theoretically for the case of directional solidification [211][212][213]. It has been found that the solidification front exhibits slow, spatio-temporal dynamics when the wavelength of the cellular convection is far longer than that of the morphological cells.…”
Section: Coupled Morphological and Convective Instabilitiesmentioning
confidence: 99%
“…Such instabilities have been analyzed theoretically for the case of directional solidification [211][212][213]. It has been found that the solidification front exhibits slow, spatio-temporal dynamics when the wavelength of the cellular convection is far longer than that of the morphological cells.…”
Section: Coupled Morphological and Convective Instabilitiesmentioning
confidence: 99%
“…В работах [8][9][10] показано их влияние на макроструктуру и морфологическую устойчивость фронта. Так в [10] показано, что гравитационная кон-векция заметно снижает критическую скорость потери устойчиво-сти плоского фронта, а в [9] получена общая диаграмма уменьше-ния области устойчивого роста при увеличении скорости потока расплава.…”
Section: Introductionunclassified
“…It has been shown in the classical work by Mullins and Sekerka [1] that the origin of this instability of the interface is related to the dependence of phase change temperature on solute concentration by considering the isotropy interface properties. Later, there appeared a great number of works that investigated the effect of solute convection, forced flows, and other factors on the morphological instability [2,3]. The effect of the slightly anisotropic surface tension and kinetics on morphological stability was studied by Cahn [4] and Coriell and Hardy [5].…”
Section: Introductionmentioning
confidence: 99%